Brain Reward System and Its Volumetric Investigations in Alcohol Addiction - Tabara, Muhammed Fatih; Atmaca, Murad; Yildirim, Hanefi; Solmaz, Onur; Essibayi, Muhammed Amir; Gurok, Mehmet Gurkan (Turkish Green Crescent Soc, 2024)
It has been shown that structural changes occur in the brain in many types of addiction and can have an impact on maintaining addictive behavior, which can be improved with treatment. The study aimed to identify structural changes in the brain's reward system in alcohol use disorder. Structural magnetic resonance imaging was employed to compare the volumes of total white matter and gray matter, as well as those of the nucleus accumbens, ventral tegmental area, amygdala, and hippocampus between 15 individuals diagnosed with alcohol use disorder and 17 healthy controls. The Michigan Alcoholism Screening Test, Severity of Alcohol Dependence Questionnaire, and Alcohol Use Disorders Identification Test were administered to the participants to reveal the pattern of alcohol use and severity of dependence. The group with alcohol use disorder exhibited a significant decrease in the volume of the right hippocampus. No differences were found between the two groups in terms of other brain regions. In conclusion, this study revealed a decrease in hippocampal volume in patients with alcohol use disorder. It is an indication that structural changes play a role in the etiology of cognitive impairments commonly seen in alcohol use disorder.
Keywords: Alcohol; brain reward system; neuroimaging; mesocorticolimbic system